Global estimates on the number of people blind or visually impaired by age-related macular degeneration: a meta-analysis from 2000 to 2020 - Furtado, João M.; Jonas, Jost B. (Eye, 2024)
We aimed to update estimates of global vision loss due to age-related macular degeneration (AMD).